Review of the Conversion of Sidewalks on Jalan Pantai Mardika, Sirimau District for Street Vendor Locations - Topurtawy, Ferni Grasia; Pinoa, Wiclif Sepnath; Sihasale, Daniel Anthoni (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
In its development, Indonesia faces challenges due to high population growth, creating an imbalance in the workforce and a shortage of jobs. Population growth positively impacts the economy but also brings negative consequences in the form of unemployment and income inequality. Many workers, especially street vendors (PKL), turn to the informal sector. Ambon City, as the center of government of Maluku Province, has experienced significant growth with urban governance problems, especially related to street vendors. The revitalization of Mardika Market is an effort to improve governance. Still, the relocation of traders creates new issues, such as changes in the function of kiosks and trading activities on the streets. A holistic approach is needed to address Indonesia's complexity in urban development. This study uses a descriptive survey method, utilizing the Arikunto (2010) approach, with a population of less than 100, making it a population study. The aim is to interpret changes in the function of sidewalks in Ambon City, especially Mardika Beach Road, into a place for street vendors to trade. The research object involved 10 street vendors. The Mardika Terminal has an essential economic role in Ambon City. Sidewalks, which should be for pedestrians, are misused as trading areas. Research shows a decline in the function of sidewalks, which is detrimental to pedestrian comfort. This conversion disrupts pedestrian activities and occurs because the Mardika market is being renovated, forcing street vendors to use the sidewalk to trade.